QUALITY COMPARISON OF NORMAL AND PSE (PALE, SOFT, AND EXUDATIVE) MEAT PORK OF LANDRACE PIG - Gertruida M. Sipahelut; Mulado Mulado (Universitas Nusa Cendana, 2014)
The quality of normal and PSE meat pork of Landrace pigs have been compared in this research. Forty commercial Landrace pigs were used in the study. Twenty pigs produce normal and the other twenty produce PSE meat. Meat pork samples were taken from eye-muscle (musculus longisimus dorsi) which located behind the last rib. Variables measured as meat pork quality indicators were pH, meat colors, and water holding capacity. The results showed that quality of normal meat pork was higher than that of PSE meat pork for all variables. Muscle pH of PSE meat pork rapidly falling in first three hours after slaughtering with pH in 45 minutes, 1 hour, 2 hours, and 3 hours were 5.78, 5.75, and 5.68, respectively; while pH of normal meat pork for the same measurements were 6.57, 6.48, and 6.30 respectively. Muscle of PSE meat was brighter that of normal meat. It was indicated by higher L*and b* coordinate values. The comparison between PSE and normal meat pork for L* & b* were 58.69 vs 53.79 and 17.07 vs 14.80 respectively. Water holding capacity of normal meat pork was higher than that of PSE meat pork. ABSTRAK Kualitas daging babi normal dan daging PSE babi Landrace telah dibandingkan dalam penelitian ini. Empat puluh babi Landrace komersial digunakan dalam penelitian ini. Dua puluh babi menghasilkan daging normal dan dua puluh menghasilkan daging PSE. Sampel daging babi diambil dari mata-otot (musculus longisimus dorsi) yang terletak di belakang tulang rusuk terakhir. Variabel yang diukur sebagai indikator kualitas daging babi adalah pH, ​​warna daging, dan kapasitas menahan air. Hasil penelitian menunjukkan bahwa kualitas daging babi yang normal adalah lebih tinggi dari PSE daging babi untuk semua variabel. pH otot daging babi PSE dengan cepat layu tiga jam pertama setelah disembelih dengan pH di 45 menit, 1 jam, 2 jam, dan 3 jam dengan pH masing-masing 5.78, 5.75, dan 5.68; sedangkan pH daging babi daging normal untuk pengukuran yang sama masing-masing 6.57, 6.48, dan 6.30. Otot daging babi PSE terang dibanding daging babi normal. Hal ini ditunjukkan dengan adanya nilai koordinat L * dan b *. Perbandingan antara L * & b * daging babi PSE dan daging babi normal masing-masing 58,69 vs 53,79 dan 17,07 vs 14,80. Kapasitas menampung air daging babi normal lebih tinggi dari PSE daging babi.